Validitas Petunjuk Praktikum Ekologi Perairan dalam Pembelajaran Mahasiswa - Safnowandi, Safnowandi (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to measure the extent to which practical instructions meet the validity criteria for use in learning aquatic ecology. This type of research is development research. The research instrument used was a validation sheet. The data collection technique uses validation. The data analysis technique uses percentage techniques. The research results showed that the validation results from content/material experts were 80% in the very good category, display experts were 87% in the very good category, and language experts were 90% in the very good category, so that the average value of the validation test results was obtained. aquatic ecology practicum instruction expert by 85%. With these results, the practical instructions that have been prepared are in the very good category and do not need to be revised.